Gender disparities in financial inclusion in Tanzania - Maureen Were; Maureen Odongo; Caroline Israel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Although Tanzania has made notable progress in enhancing access to financial services, the gender gap in financial inclusion persists. This paper examines gender disparities in financial inclusion in Tanzania using descriptive and regression analyses. While the advent of mobile phone money services has led to increased access to formal financial services, women still lag behind in access to and utilization of formal financial services. Based on FinScope Tanzania survey data for 2017, the empirical results show that women-especially married women-are less likely to access mobile money services and banking financial services compared with men. Similarly, women are less likely to save and borrow compared with men, with a higher percentage opting to keep cash at home or save with a saving group. The gender gaps in financial inclusion are attributable to factors such as lack of income, limited financial literacy, and lack of access to smartphones and other digital facilities. There is a need to be cognizant of gender differences in preferences. Policy initiatives to enhance access to digital financial services, improve women's education and financial literacy, and promote saving groups are critical to enhance women's access to formal financial services.
Keywords: G00; G21; G23; G5; 330; gender; financial inclusion; mobile money; Tanzania